The Legal Politics of Halal Tourism in Thailand: The Impact of Digital Advertising Interventions on Consumer Intent, Recommendations, and Engagement in the Contemporary Era - Immanuel Ustradi Osijo; Fulgentius Danardana Murwani; Ery Tri Djatmika; Sopiah; Rungarun Boonsayan (Faculty of Sharia, IAIN Metro, 2024)
This study explores the legal politics of halal tourism in Thailand by highlighting the impact of digital advertising interventions on consumer intent, recommendations, and engagement. Thailand, as a leading global tourist destination, is increasingly expanding its halal tourism sector but faces challenges in aligning the needs of Muslim travelers with effective digital promotion strategies. This research analyzes how digital advertising can influence consumer perceptions and decisions, especially in the contemporary era of globalization and digital transformation. With a qualitative approach, this study uses data from literature studies, interviews with tourism industry players, and analysis of Thai government policies related to halal tourism. The findings show that the right digital advertising interventions can increase Muslim tourists' intention to visit, encourage positive recommendations, and strengthen consumer engagement. In addition, legal policies supporting halal tourism promotion are essential in creating competitive attraction in the global market. The results of this study contribute to the understanding of the political law of halal tourism in Thailand, as well as offer strategic recommendations for the government and industry players to utilize digital advertising in supporting the growth of this sector. The implications of this research are also relevant in building a sustainable halal tourism ecosystem amid the dynamics of the contemporary era.